Portable laser ablation sheds light on Early Bronze Age gold treasures in the old world: new insights from Troy, Poliochni, and related finds - Numrich, Moritz; Schwall, Christoph; Lockhoff, Nicole; Nikolentzos, Kostas; Konstantinidi-Syvridi, Eleni; Cultraro, Massimo; Horejs, Barbara; Pernicka, Ernst (Journal of archaeological science, 2023)
The paper focuses on the archaeometric analyses of the gold objects from the famous so-called ‘treasures’ of Troy and Poliochni on the island of Lemnos. Altogether 61 Early Bronze Age (EBA) gold objects dating between 2500 and 2000 BCE were investigated in this study. They were primarily sampled with a portable laser ablation (pLA) unit in the National Archaeological Museum in Athens and analyzed with ICP-MS at the Curt-Engelhorn-Centre Archaeometry (CEZA) in Mannheim. The main advantage of this approach is the possibility to obtain samples on site without the necessity of transport. It is a minimally invasive method that leaves no visible damage on the objects. As an additional advantage there are no restrictions on the size of the objects under study. The central goal of the study was to obtain high-quality compositional analyses of gold objects from the sites Troy and Poliochni to investigate, if the typological similarity is paralleled by the elemental composition of the gold, including the trace elements. This would suggest not only similar procurement of the metal across these sites but also potential exchange of objects and/or specialist workers. In a second step, the results were compared with data from contemporary gold objects from Ur in southern Mesopotamia, from where LA-ICP-MS data have recently become available. Finally, a survey of such data for gold objects from gold-rich regions is used to narrow down the possible origin of Early Bronze Age gold in the Old World.
Available online 29 November 2022
Gesehen am 09.02.2023